Pharmacological induction of CCL5 in vivo prevents gp120-mediated neuronal injury. (May 2015) - Campbell, Lee A.; Avdoshina, Valeriya; Day, Chris; Lim, Seung T.; Mocchetti, Italo
Abstract: The human immunodeficiency virus (HIV) envelope protein gp120 promotes neuronal injury which is believed to cause HIV-associated neurocognitive disorders. Therefore, blocking the neurotoxic effect of gp120 may lead to alternative strategies to reduce the neurotoxic effect of HIV. In vitro, the neurotoxic effect of M-tropic gp120BaL is reduced by the chemokine CCL5, the natural ligand of CCR5 receptors. To determine whether CCL5 reduces the toxic effect of gp120BaL in vivo, animals were intrastriatally injected with lentiviral vectors overexpressing CCL5 prior to an intrastriatal injection of gp120BaL (400 ng). Neuronal injury was determined by silver staining, cleaved caspase-3 and TUNEL. Overexpression of CCL5 decreased gp120-mediated neuronal injury. CCL5 expression can be up-regulated by chronic morphine. Therefore, we examined whether morphine reduces the neurotoxic effect of gp120BaL. Rats stereotaxically injected with gp120BaL into the striatum received saline or chronic morphine for five days (10 mg/kg escalating to 30 mg/kg twice a day). Morphine-treated rats showed a decrease in all markers used to determine neuronal degeneration compared to saline-treated rats. The neuroprotective effect of morphine was significantly attenuated by expressing CCL5 shRNA. Our results suggest that compounds that increase the endogenous production of CCL5 may be used to reduce the pathogenesis of HIV-associated neurocognitive disorders. Highlights: We show that the HIV protein gp120BaL causes synaptic degeneration in vivo . Morphine abuse and withdrawal differentially affect gp120 neurotoxic effect. CCL5 plays a role in the neuroprotective effect of morphine in vivo .